Use of psychoactive drugs predicts functional disability among older adults - Denise Mourão Falci; Juliana Vaz de Melo Mambrini; Érico Castro-Costa; Josélia Oliveira Araújo Firmo; Maria Fernanda Lima-Costa; Antônio Ignácio de Loyola Filho (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE: Investigate whether the use of psychoactive drugs would be a predictor of incidence of functional disability among seniors living in community. METHODS: It is a population-based longitudinal study, developed between January 1, 1997 and December 31, 2011, with older adults living in community. The association between the use of psychoactive drugs and the development of functional disability for instrumental (IADLs) and basic (BADLs) activities of daily living was tested using the extended Cox proportional hazards model, which considers the measure of exposure of interest throughout the follow-up period. The analyses were stratified by sex and adjusted by sociodemographic characteristics, health behavior and health conditions. RESULTS: After multivariate adjustment, the use of two or more psychoactive drugs in the female stratum was associated with disability for both IADLs (HR = 1.58; 95%CI 1.17-2.13) and BADLs (HR = 1.43; 95%CI 1.05-1.94), the use of benzodiazepines was associated with disability for IADLs (HR = 1.32; 95%CI 1.07-1.62), and the use of antidepressants was associated with disability for both IADLs (HR = 1.51; 95%CI 1.16-1.98) and BADLs (HR = 1.44; 95%CI 1.10-1.90). In the male stratum, the use of antipsychotics was associated with disability for IADLs (HR = 3.14; 95%CI 1.49-6.59). CONCLUSIONS: The study showed a prospective association between the use of psychoactive drugs and functional disability. These results indicate the need to carefully assess the prescription of psychoactive drugs for older adults and monitor their usage in order to detect damages to the health of users.